Kompetisi Tanaman Jagung dan Ubikayu dalam Sistem Tumpang Sari - , Suwarto; Sudirman Yahya; , Handoko; Muhammad Ahmad Chozin (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Intercropping system of maize and cassava has been practiced widely by Indonesian farmer on dry land. Competition between the plant will happen in the system. Field experiment to understand about the competition has been conducted. Field experiment of growing maize (Arjuna, Pioneer 4, and Cargill 9 in various planting densities) and cassava (Adira 1) was conducted for monoculture and intercropped plants. Intercropped cassava increased intraspesific competition of maize. Yield of maize variety of Arjuna, Pioner 4, and Cargill 9 decreased by about 9.7%, 6.7%, and 16.9% respectively. Maize also reduced growth and yield of cassava. When intercropped with Arjuna, pioner 4, and Cargill 9 at the highest density (80 000 plants ha-1), yield of cassava tuber decreased by about 40.6%, 43% and 64.3%, respectively. However, the intercropping still gave a better land productivity, where land equivalent ratio (LER) was larger than 1.0. Key words: intercropping, competition, maize, cassava